Discrete Event Simulation untuk Analisis Pelayanan Bisnis Kuliner (Studi Kasus : Gacoan Merr) - Shofiudin, Muhammad; Nur Aini, Salsabilla Annafi’u; Ihsan, Muhammad Sakhil; Wibowo, Raya Akbar Tiar; Rolliawati, Dwi (Universitas Boyolali, 2024)
A queue is a group of people or goods in a line waiting to be served. It can occur when the number of visitors is greater than the number of serving resources. One of these queuing phenomena can be found at one of the fast food outlets, namely Gacoan Merr Surabaya. This study aims to identify and analyze the factors that affect queues and propose a more efficient strategy to solve queuing problems at Gacoan Merr Surabaya. The simulation model used is a discrete-event simulation model. The method in this study has stages that include problem analysis, literature study, observation, system modeling, and proposed solutions. The variables used in the research object include the time interval of arrival, the number of customers, the total number of servers in the ordering service process, and the total number of servers in the food manufacturing process, for a total of eight people. From the results of system modeling, it is found that the use of eight servers in the product processing phase can still be said to be less effective where the food distribution time also takes longer. Therefore, changes are needed in the product or food manufacturing phase by adding the number of servers used to process orders. The increase in the number of servers shows a decrease in the number of order queues in the product processing phase, and the food distribution time becomes faster.